The Loricrin-Like Protein (LLP) of Phytophthora infestans Is Required for Oospore Formation and Plant Infection - Guo, Ting; Wang, Xiao-Wen; Shan, Kun; Sun, Wenxian; Guo, Li-Yun (Frontiers in Plant Science, 2017)
Loricrin-like protein (LLP) is characterized by a high content of glycine residues and is a major component of plant cell wall. Here, we identified a Phytophthora infestans ortholog of plant LLP, named PiLLP. In P. infestans, PiLLP is strongly expressed in asexual and sexual developmental stages, including in sporangia, zoospores and germinating cysts, and during oospore formation, as well as in the early stages of infection and during hydrogen peroxide stress. Compared with the wild type, the PiLLP-silenced transformants were defective in oospore formation, had slower colony expansion rates, produced less sporangia with lower germination and zoospore-release rates, and were more sensitive to hydrogen peroxide. Moreover, Nile red staining and PiLLP-red fluorescent protein fusions indicated that PiLLP is involved in oogonia formation. The silenced transformants also had severely diminished virulence levels that could be partially restored with diphenyleneiodium treatments. The analysis of catalase activity showed a decrease of catalase activity in silenced transformants. Thus, PiLLP is important for sexual and asexual reproduction, and is required for oxidative stress tolerance and plant infection.